Presidential Nominations from Active Cabinet Ministers: A Delicate Balance between the Interpretation of Constitutional Court Decisions and Political Interests - Zaini, Ahmad; Jambunanda, Ahmad Jamaludin; Ishom, Muhammad; Sunardi, Dedi; Pudoli, Asep (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
The Constitutional Court’s Decision number 68/PUU-XX/2022 has sparked substantial debate among various societal factions. The controversy stems from the interpretation that the ruling potentially enables ministers to misuse their authority and exploit state resources for electoral advantages while running for President or Vice President, without necessitating resignation from their current position. This study seeks to discern the ramifications of the Constitutional Court's decision number 68/PUU-XX/2022 on the roles and authorities of ministers within a presidential government structure, and to scrutinize the decision from an Islamic law/siyasah perspective. This investigation adopts a descriptive qualitative approach, grounded in library research. The normative juridical methodology is employed, focusing on decision number 68/PUU-XX/2022. The study concludes that within the context of siyasah sharia, the decision could compel the nation’s leader (the President) to promulgate legal regulations that violate the principle of fairness between high-ranking and ordinary officials. However, the President risks being deemed unconstitutional if derivative regulations stemming from the decision are not enacted. Power abuse by state officials (ministers), partly driven by conflict of interest, is a critical concern. From the perspective of Islamic law/siyasah, the decision’s implications could potentially harm society and the government.